2017
DOI: 10.1186/s40659-017-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Alpinia oxyphylla Miq. extract changes miRNA expression profiles in db-/db- mouse kidney

Abstract: BackgroundA number of dysregulated miRNAs have been identified and are proposed to have significant roles in the pathogenesis of type 2 diabetes mellitus or renal pathology. Alpinia oxyphylla has shown significant anti-inflammatory properties and play an anti-diabetes role. The objective of this study was to detect the alteration of miRNAs underlying the anti-diabetes effects of A. oxyphylla extract (AOE) in a type II diabetic animal model (C57BIKsj db-/db-).ResultsTreatment with AOE for 8 weeks led to lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Previous studies have shown that A. oxyphylla can promote the migration and proliferation of human adipose tissue-derived stromal cells [ 21 , 22 ]. In our previous study, we found that A. oxyphylla extract (AOE) exhibits an antioxidant and anti-T2DM capacity [ 23 , 24 ]. However, the mechanism of AOE-mediated anti-T2DM function remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that A. oxyphylla can promote the migration and proliferation of human adipose tissue-derived stromal cells [ 21 , 22 ]. In our previous study, we found that A. oxyphylla extract (AOE) exhibits an antioxidant and anti-T2DM capacity [ 23 , 24 ]. However, the mechanism of AOE-mediated anti-T2DM function remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The huge amount of NKT and simple extraction mean it is easily obtained and has been applied as a functional ingredient of health foods or medical agents to prevent disorders or diseases. More interestingly, the extracts of A. oxyphylla have been used to improve urinary and renal functions, such as polyuria, hyperuricemia [8], and diabetic nephropathy in animal models [10,49]. These findings provided empirical evidence to speculate a possible excellent preventive candidate such as NKT to mitigate the progression of kidney diseases.…”
Section: Discussionmentioning
confidence: 97%
“…It has also been broadly used as the traditional medicine for the treatment of diarrhea, ulceration, and enuresis [7]. Its fruit extracts revealed an anti-hyperuricemic effect in the kidney [8], hepatoprotective function against CCl 4 -induced oxidative damage in vitro and in vivo [9], and anti-diabetic action [10]. Recent pharmacological evidence indicated that one of the important active ingredients of A. oxyphyllae, nootkatone (NKT), exhibited excellent protective and inhibitory effects on inflammation and apoptosis in neuronal cells [11], displayed improved properties against particle-induced lung injury in mice, and also prevented fibrotic actions and inflammatory response in a liver injury murine model [12].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, db/db mice, as the model of type 2 DN with significant hyperglycemia and insulin resistance, are the excellent obesity model with the leptin receptor gene mutation, whose renal lesions is not severe (Kitada et al, 2016). Secondly, wild type mice, instead of db/m, was used as a normal control, since it was reported that wild type mice better reflected the normal state of miRNA expression, and wild type littermates were reported to be superior to db/m as normal controls when performing miRNA sequence analysis (Du et al, 2017). Thirdly, QDTS with multi-components might offer reno-protective effects by modulating multi-targets, which makes much difficulty to support the causal relationship between nutrient-sensing signaling molecules and kidney damage directly, since it is difficult to demonstrate a causal relationship by only blocking one pathway.…”
Section: Discussionmentioning
confidence: 99%